Antibiotic susceptibility of Salmonella, Shigella and Vibrio isolated from diarrhea patients in Jakarta, Indonesia - Meiyanti Meiyanti; Oktavianus Ch Salim; Elly Herwana; Joice V kalumpiu; Murad Lesmana (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2016)
Background: The rapid increase of antibiotic resistance among enteric pathogens in developing countries has become a great concern. In Indonesia, Salmonella, Shigella, and Vibro are still an important public health problem. Objectives: The purpose of this study was to determine the antibiotic resistance patterns of several diarrhea-causing enteric bacteria that are frequently found in Indonesia, particularly Salmonella, Shigella and Vibrio. Methods: A cross-sectional study was conducted , among 150 rectal swabs collected from patients with diarrhea, the enteric pathogens isolated comprised Shigella (11.4%), Salmonella (6.6%) and Vibrio(2.7%). Results: Antibiotic susceptibility test on Shigella species to several antibiotics such as ampicillin, chloramphenicol, tetracycline and, trimethoprim-sulfamethoxazole showed a considerably high resistance rate (25%-100%), whereas ceftriaxone, ciprofloxacin, norfloxacin and nalidixic acid were apparently still effective (resistance rate 0%). Non-typhoid Salmonella had similar resistance patterns as those of Shigella, particularly to ampicillin, tetracycline, chloramphenicol and trimethoprim- sulfamethoxazole However, for S. typhi it was found that all antibiotics were still effective. Vibrio was resistant to ampicillin (resistance rate 100%), whereas the other antibiotics were still effective. Conclusion: It may be concluded that for each of the enteric pathogens the antibiotic resistance pattern should be determined. Use of antibiotics should be based on the antibiotic susceptibility tests.